The effect of residual and distillate fuel on camshaft & electronically controlled marine diesel engines combustion and performance - Hountalas, Theofanis (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Θερμότητας. Εργαστήριο Ετερογενών Μειγμάτων και Συστημάτων Καύσης, 2016)
Inspired by the recent changes in environmental regulations and my yearlong interest in marine engines this project focuses on the consequences from the use of distilled low sulfur marine gas oil (MGO) on engines that were originally designed to operate on undistilled heavy fuel oil (HFO). The two fuel types’ great differentiations in physical characteristics (i.e. viscosity and heating value) and the fact that most marine engines and fuel systems were developed to operate on HFO make the comparison both interesting and meaningful. As described in the text the long term of MGO is obligatory in specific areas for which strict emission legislations related to the sulfur content of the fuels are applicable. The cases investigated in the present study include two 4-stroke, medium speed auxiliary engines (diesel generators) and four 2-stroke, low speed main propulsion engines, the one being a conventional MC type engine and the other three modern electronically controlled ME engines (the system widely known as common rail) of various types and generations. The previous has been done in an effort to include the most important engine designs that are now operating on the field. The data used for analysis were obtained at various operating conditions in an effort to cover the entire operating range of the engine i.e. form low to high load. Most of the data used in the present work were acquired under actual operating conditions i.e. at sea using in house instrumentation and specifically a diagnosis system which is used for engine performance monitoring. For the modern 2-stroke electronic engines measurements were also acquired on the test bench after having obtained special permission from the engine maker to attend the shop tests. For one case measured data were acquired from a commercial system installed on the vessel that provided fuel injection pressure data which was valuable for the analysis. The utilization of the fuel pressure data provided a significant contribution towards the understanding of the fuel type effect on the engine injection system. These data were provided as hardcopy and for this reason they had to be processed (digitizing) in order to obtain the data in digital format. For this purpose, a special technique was used to obtain the data from the pdf files since the graphs were in vector format. The software for data processing and for the heat release rate analysis was written in Fortran. From the processing of data, it was revealed that specific effort and care is required in order to distinguish the actual effect of fuel properties on engine performance and combustion. The main source of data used for the analysis and for the determination of fuel type effect on combustion is the cylinder pressure diagram. But as revealed from the analysis, this is also affected by the measurement procedure and from the engine settings and especially from the start of fuel injection. Another important finding was that usually it is not possible to derive safe results directly from the cylinder pressure trace if differences exist in compression pressure and or start of injection. In most cases small differences in the start of injection can have a more significant effect when compared to the one of fuel type. From the processing of data valuable results were derived revealing that there is an impact of the fuel type on engine performance and on the combustion mechanism. The resulting effect can range from very small to quite significant, which depends on the engine type and its condition. Another important finding revealed from one of the cases examined isthe possibility of a fuel injection system problem when operating on MGO due to its physical properties and low lubricity and viscosity. The differences were quite subtle in the case of the modern electronic 2-stroke engines and more evident in the case of the conventional 2-stroke camshaft one. Fuel effect was clearly more pronounced in the case of the 4-stroke auxiliary engine used for on-board power generation whose high rotational speed enhance the differences when expressed in degrees of crank angle. This is to be expected since these engines are much more sensitive to engine settings, etc. due to the higher rotational speed. From the present investigation it results that the factors affecting engine operation are many and interact in complicated and often conflicting ways. For this reason, providing general, conclusive and detailed results for all engine types based on this preliminary investigation is not the correct way for proceeding. However, the findings from the present Thesis are important, since a clear effect of the fuel type on engine performance and combustion is revealed. Furthermore, important issues have been defined that have to be considered when conducting such an analysis, related mainly to the measurement procedure and the processing methodology. This information is important for supporting future investigations that are definitely required.